Negociando el multiculturalismo : dinámicas sociopolíticas del reconocimiento a los afrocolombianos - Estupiñan Bejarano, Juan Pablo (2017)
This thesis is about the negotiations of inclusion of Afro-Colombians in multiculturalism, understood as a form of government of populations based on cultural difference, but in which the limits of that difference that is recognized and managed politically are in permanent reconfiguration. Using the ethnographic approach (as a method of research and text description) I take various senses about the Afro-Colombian cultural difference, and how they are re-signified and mobilized in three universes where it is possible to approach the particularities of the multicultural project in Colombia: the negotiations for the categories in the censuses, the negotiations around the policy of reparation to victims, and the negotiations about their afropacific music. In each universe I identify the social actors that converge, the articulations, tensions and sonorities that come from these interactions, in order to identify the senses about Afro-Colombian ethnicity that are (re)configured and the associated socio-political dynamics. The analysis of this three proposed ethnographic universes allows me to conclude with a critical look on the Colombian multicultural project in the current post-conflict scenario, and how the anthropological practice is inscribed in this context.